THE CONCEPTUAL EVOLUTION OF LISTENING IN INDONESIAN ENGLISH CURRICULA: A QUALITATIVE DOCUMENT ANALYSIS OF THE 2006 KTSP, THE 2013 CURRICULUM, AND THE MERDEKA CURRICULUM - Nurhayati Ganinda; Rini Lindawati; Asih Andriyati Mardliyah (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
Although changes in the Indonesian English curriculum have been widely studied, previous research has primarily focused on curriculum implementation, teachers’ perceptions, and instructional practices. Little attention has been given to how listening has been conceptually represented across successive curriculum reforms. This study investigates the conceptual evolution of listening in Indonesian junior secondary school English curricula, covering the 2006 School-Based Curriculum (KTSP), the 2013 Curriculum, and the Merdeka Curriculum. Adopting a qualitative approach with a Qualitative Document Analysis (QDA) design, the study analyzed official curriculum documents through thematic coding of curriculum objectives, learning outcomes, and descriptions related to listening. The findings reveal a three-stage conceptual evolution: listening as a receptive skill, listening as text comprehension, and listening as integrated communicative competence. While the 2006 KTSP conceptualized listening as understanding spoken meaning, the 2013 Curriculum embedded listening within a genre-based approach, and the Merdeka Curriculum integrated listening with speaking as a unified communicative competence. These findings indicate that curriculum reform reflects not only structural changes but also a shift in the underlying conceptualization of listening. This study proposes a conceptual evolution framework that contributes to curriculum research and provides insights for future English language curriculum development and listening pedagogy.